Replication data for: Enchaînement, liaison, accentuation chez les apprenants norvégiens ... - Andreassen, Helene N.; Lyche, Chantal (DataverseNO, 2015)
[abstract] Given that their L1, Norwegian, and their L2, English, are lexical stress languages, Norwegian speakers will equally tend to stress lexical words during the course of acquisition of L3 French, insuring the prosodic autonomy of each word. In the present paper, we show that this strategy slows down the acquisition of two external sandhi phenomena in French, i.e. liaison and final consonant linking. The data, taken from two corpora recently collected in Tromsø and Oslo, indicate that the learners' acquisition path is conditioned by internal factors like prosodic weight, perceptual salience and frequency, and by external factors like the different tasks to be completed, i.e. reading vs conversation. The data further indicate that liaisons following determiners and clitics are the first categories to be acquired and that spontaneous speech, where the learner does not have direct access to the graphic word, seems to favor erasing the prosodic boundaries required by the prosodic system of her L1. ...